2013
DOI: 10.1371/journal.pone.0082001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of LRRK2 in Taiwanese Parkinson’s Disease

Abstract: Genetic variants of leucine-rich repeat kinase 2 (LRRK2) were reported to alter the risk for Parkinson’s disease (PD). However, the genetic spectrum of LRRK2 variants has not been clearly disclosed yet in Taiwanese population. Herein, we sequenced LRRK2 coding region in 70 Taiwanese early onset PD patients (age at onset ≤ 50), and found six amino acid-changing single nucleotide polymorphisms (SNPs, N551K, R1398H, R1628P, S1647T, G2385R and M2397T), one reported (R1441H) and 2 novel missense (R767H and S885N) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
5
30
1
Order By: Relevance
“…Interestingly, Wu et al recently described that a LRRK2 p.S1647T-p.M2397T haplotype appeared to have a protective effect against PD in a large Taiwanese cohort [12]. Although the protective haplotype was not able to counteract with genetic effect on the PD risk of the p.G2385R, it seemed to decrease in risk of developing PD of the other carriers (OR ¼ 0.8, 95%CI ¼ 0.65e0.97) including carriers of the p.R1628P [12]. Our finding was quite different; all Thai carriers of the p.R1628P had p.S1647T-p.M2397T haplotype, and they were still more susceptible to develop PD than the non-carrier group.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, Wu et al recently described that a LRRK2 p.S1647T-p.M2397T haplotype appeared to have a protective effect against PD in a large Taiwanese cohort [12]. Although the protective haplotype was not able to counteract with genetic effect on the PD risk of the p.G2385R, it seemed to decrease in risk of developing PD of the other carriers (OR ¼ 0.8, 95%CI ¼ 0.65e0.97) including carriers of the p.R1628P [12]. Our finding was quite different; all Thai carriers of the p.R1628P had p.S1647T-p.M2397T haplotype, and they were still more susceptible to develop PD than the non-carrier group.…”
Section: Discussionmentioning
confidence: 87%
“…As mention earlier, the negative studies were likely to result from inadequate sample sizes in relation to a paucity of the variant in the population studied. Interestingly, Wu et al recently described that a LRRK2 p.S1647T-p.M2397T haplotype appeared to have a protective effect against PD in a large Taiwanese cohort [12]. Although the protective haplotype was not able to counteract with genetic effect on the PD risk of the p.G2385R, it seemed to decrease in risk of developing PD of the other carriers (OR ¼ 0.8, 95%CI ¼ 0.65e0.97) including carriers of the p.R1628P [12].…”
Section: Discussionmentioning
confidence: 92%
“…Totally, 14 studies711131520212223242526272829 were included from across all the ethnic Han-Chinese population that mainly located in Mainland China, Singapore and Taiwan. Process of searching for and screening studies was showed in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Only 2 studies722 in ethnic Han-Chinese with familial PD and 11 studies711152021232425262728 in ethnic Han-Chinese with sporadic PD were analyzed to evaluate the overall level for association between familial (Fig. 4A) or sporadic (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation